2019
DOI: 10.1097/meg.0000000000001360
|View full text |Cite
|
Sign up to set email alerts
|

Effectiveness of 8-week sofosbuvir/ledipasvir in the adolescent chronic hepatitis C-infected patients

Abstract: Background The sustained virological response (SVR) rate for the 12-week sofosbuvir (SOF)/ledipasvir (LVD) treatment of adolescent genotype-4 patients is high. The aim of this study is to evaluate 8 versus 12-week treatment efficacy and safety in adolescent genotype-4 patients. Patients and methods In total, 157 chronic hepatitis C-infected adolescent patients (mean age 14±2 years, 62% males) were included in this study. All patients received a morning … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
30
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(32 citation statements)
references
References 34 publications
2
30
0
Order By: Relevance
“…We did not detect any significant differences between the various treatment durations in terms of efficacy in adolescents or children (P b = 0.398, P d = 0.716). Hesham et al also found that 8 weeks of treatment with the SOF/LDV combination was as effective and safe as the 12-week regimen in adolescent GT4 patients (15). Similar results were reported by Mortada et al (38).…”
Section: Discussionsupporting
confidence: 62%
See 1 more Smart Citation
“…We did not detect any significant differences between the various treatment durations in terms of efficacy in adolescents or children (P b = 0.398, P d = 0.716). Hesham et al also found that 8 weeks of treatment with the SOF/LDV combination was as effective and safe as the 12-week regimen in adolescent GT4 patients (15). Similar results were reported by Mortada et al (38).…”
Section: Discussionsupporting
confidence: 62%
“…Common AEs included fatigue, nausea, and so on. The SAEs were defined as any event causing disability, congenital malformation, or death (8,(15)(16)(17). The worsening of laboratory test values from baseline was graded using the National Cancer Institute Common Terminology Criteria for Adverse Events (18).…”
Section: Research Outcomesmentioning
confidence: 99%
“…In total, 39 references met the inclusion criteria. Twenty‐eight papers were published as full‐text articles 3‐8,11‐32 and 11 as abstracts 33‐43 . Two studies were randomised clinical trials, 27,33 whereas all the other studies were nonrandomised studies.…”
Section: Resultsmentioning
confidence: 99%
“…98.6% for the 12-and 8-week regimen, respectively). 68 The same authors also reported an SVR12 rate of 99% after 12 weeks of SOF/ LED in 144 adolescent chronic HCV patients with genotype 4. 69 In a final observational study, 40 Egyptian children and adolescents with HCV genotype 4 (age ranging from 11.5 to 17.5 years) were treated with 12 weeks of SOF/LED, resulting in an SVR12 rate of 100%.…”
Section: Direct-acting Antiviral Agentsmentioning
confidence: 89%